A Case of Congenital Common Bile Duct Web Treated with Balloon Dilation under Endoscopic Retrograde Cholangiopancreatography in a Young Child - Ji Sook Park; Hong Jun Kim; Ji-Hyun Seo; Hee-Shang Youn (Korean Society of Gastrointestinal Endoscopy, 2021)
Web in common bile duct (CBD web) is very rare. It is usually asymptomatic and detected incidentally during surgery for other causes in adults. It can be congenital or acquired, however congenital CBD web is extremely rare. Currently, despite its invasiveness and complications, endoscopic retrograde cholangiopancreatography (ERCP) is considered as a useful diagnostic and therapeutic modality in children with hepatobiliary pancreatic diseases as in adults. Herein we report a case of congenital CBD web presenting with acute pancreatitis and choledocholithiasis in a 4-year-old girl which was diagnosed and treated using balloon dilation under ERCP. After balloon dilation of the web, a common pancreatobiliary channel was observed. To the best of our knowledge, a case of congenital CBD web with pancreatobiliary junctional abnormality treated using ERCP in a child has not been reported to date.